Festival & special event management - Allen, Johnny; O'Tootle, William;Harris, Robert;McDonnell, Ian (Australia : John Wiley & Son, Inc., 2008)
Festival and special event management fourth edition continues the comprehensive overview of the theory and procedures associated with festivals and special events established in previous editions.
Part 1 : Event context -- Part 2 : Planning -- Part 3 : Event operations and evaluation -- Part 4 : Legal, risk, and OHS management
Includes index.
Keywords: FESTIVALS -- MANAGEMENT